Calibration and evaluation of the DSSAT/Canegro model for sugarcane cultivars under irrigation managements - Coelho, Anderson P. [UNESP]; Dalri, Alexandre B. [UNESP]; Fischer Filho, Joao A. [UNESP]; De Faria, Rogerio T. [UNESP]; Silva, Laercio S. [UNESP]; Gomes, Romario P. [UNESP] (Univ Federal Campina Grande, 2020)
Model calibration is a fundamental factor to obtain high accuracy in the estimation of crop growth and yield. This study aimed to parameterize the genetic and ecotype coefficients of the DSSAT/Canegro model for five sugarcane cultivars kept under three water managements, besides evaluating the accuracy of the model in predicting sugarcane stalk yield, sugar yield and height. Experimental field data were obtained from two years (2016 and 2017) of cultivation at FCAV/Universidade Estadual Paulista, Jaboticabal, SP, Brazil. The cultivars were maintained under supplementary irrigation, deficit irrigation and no irrigation. Data of the supplementary irrigation treatment (without stress) were used for the parameterization of each cultivar. Model accuracy was assessed by Pearson correlation (r), root mean squared error (RMSE), mean bias error (MBE), index of agreement (d) and confidence coefficient (c). The DSSAT/Canegro model is highly accurate in predicting stalk and sugar yields of sugarcane grown under water regimes, presenting itself as a viable alternative in sugarcane yield simulation. For better performance of the DSSAT/Canegro model, it is necessary to parameterize the variables related to the ecotype of the cultivars, besides the specific coefficients of the cultivars.
Keywords: Sacharum spp.; crop model; parameterization; yield